Frequency of Second Mesiobuccal Canal in Permanent Maxillary Molars: An Observational Study (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: The success of root canal therapy in endodontics is heavily dependent on identifying a second mesiobuccal canal (MB2) in permanent maxillary molars. A comprehensive understanding of internal anatomy, particularly the recognition of MB2, is crucial for the effective treatment of this commonly encountered tooth. This study aimed to investigate the prevalence and occurrence of the second mesiobuccal canal in permanent maxillary first and second molars.Methods: This cross-sectional study that was conducted at the Department of Conservative Dentistry & Endodontics, Military Dental Centre Dhaka, Bangladesh from January 2018 to December 2018.  The analysis involved a total of 200 maxillary first molars and 200 maxillary second molars. In the initial phase for both groups, teeth were examined with the naked eye followed by microscopic assessment. Data analysis was conducted with MS Office tools.Results: In naked eye observation, the frequency of MB2 canals in the first molar teeth was found 64%, and in the second molar teeth it was found 56%. On the other hand, by microscopic assessment, the frequency of MB2 canals in the first molar teeth was found 96%, and in the second molar teeth, it was found 84%.Conclusion:  The occurrence of the second mesiobuccal canal (MB2) in permanent maxillary first molars is more common than in the second molars. Microscopic assessment proves to be more effective than naked eye assessment for detecting the presence of MB2 in both maxillary first and second molars.J Bangladesh Coll Phys Surg 2024; 42: 133-138